Tilapia by-product hydrolysate powder in diets for Nile tilapia larvae - Cesar Sary; Leandro Daniel de Paris; Daniela Miotto Bernardi; Vanessa Lewandowiski; Altevir Signor; Wilson Rogério Boscolo (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to evaluate the digestibility of tilapia by-product protein hydrolysate powder (TBHP) from tilapia filleting by-product, and its inclusion in diets for Nile tilapia larvae. In order to determine the apparent digestibility coefficients, two diets were formulated, the reference diet and the test diet (20% of TBHP) and, to evaluate the inclusion, six diets were formulated, which were with 0.0, 2.0; 4.0; 6.0, and 8.0% of TBHP. The apparent digestibility coefficients of crude protein and gross energy were 89.5 and 98.3%, respectively. At levels above 4.0% of inclusion of TBHP, the weight, final length and weight gain were impaired, however, survival rate was higher (p < 0.05). The TBHP can be used in diets for tilapia due to the high digestibility coefficients for crude protein and gross energy. The inclusion of up to 4.0% of TBHP does not affect the reproductive performance and survival rate of Nile tilapia larvae.